Clinical characteristics and treatment for laryngeal cyst in children: a case series study - Zhou, Pei; Zhong, Lili; Ding, Xiaofang; Moslehi, Mohammd Ashkan; Liu, Silan; Peng, Li; Huang, Han (Frontiers in Surgery, 2025)
PurposeThis study aims to present a case series of pediatric laryngeal cysts and summarize their clinical characteristics and treatment outcomes.MethodsThis retrospective case series study included pediatric patients with laryngeal cysts at the author's Hospital, and clinical data were analyzed.ResultsA total of 20 patients were included. Among them, 15 children were diagnosed with supraglottic cysts, while five were categorized into the glottic and subglottic groups. The primary symptoms included stridor (16/20, 80%), shortness of breath (15/20, 75%), coughing after feeding (12/20, 60%), cyanosis (7/20, 35%), and Spo2 < 95% (8/20). Bronchoscopy revealed single or multiple transparent or semitransparent cystic masses capable of causing varying degrees of compression of the epiglottis or airway obstruction. Thirteen children with supraglottic laryngeal cysts underwent endoscopic plasma cyst ablation, while five children in the glottic and supraglottic areas underwent bronchoscopic titanium laser ablation. Almost all patients showed significant symptom improvement after treatment. None of the other children (18/20, 90%) experienced a recurrence during the 2 to 36-month follow-up period.ConclusionBronchoscopy should be considered for children experiencing stridor, shortness of breath, coughing after feeding, cyanosis, and Spo2 < 95%. Treatment choice between endoscopic plasma cyst ablation and bronchoscopic titanium laser ablation depends on cyst type.